Effect of Supplementation of β-carotene on Milk Yield and Compositions, Somatic cell count, Dry Matter Intake, Nutrients Digestibility and Nutrient Execration in Lactating Crossbred Sahiwal Cows - Bhateshwar, Vinod; Rai, Dinesh Chandra; Duary, Raj Kumar; Rathaur, Aman; Singh, Uday Pratap (Indian Journal of Dairy Science, 2021)
This study investigated the effect of supplementation of β-carotene on milk yield and compositions, somatic cell count, dry matter intake, nutrients digestibility and nutrient execration in lactating crossbred Sahiwal cows. Twenty four crossbred (H.F. X Sahiwal) Sahiwal cows with a close date of calving were divided in two homogeneous groups for parity (4.62 ± 0.46) and milk production level within the current lactation (8.57 ± 0.08 kg/day of mature equivalent milk). All treatments were based on impromptu dry fodder (wheat straw) and lucerne as a green fodder. During the lactation period, the cows of the BETA-group were fed a diet supplemented with 500 mg/cow/day of β-carotene. Compared to CONT-group (control), BETA-group (β-carotene supplementation diet) failed to increase body weight, dry matter intake and digestibility of crude protein (CP), crude fiber (CF) and nitrogen free-extract (NFE) except ether extract (EE) significantly increased in BETA-group at p < 0.01. Overall daily milk yield (DMY), total milk yield (TMY), 3.5% fat corrected milk (FCM), energy corrected milk (ECM), milk fat yield, milk protein yield, milk lactose yield, milk solid not-fat (MSNF) and milk solid matter (MSM) were similar between treatments at p < 0.05. No differences were observed in allover milk components as fat % content (3.36 ± 0.03), milk protein % content (3.08 ± 0.04), milk lactose % content (4.25 ± 0.03), MSNF % content (7.48 ± 0.03), and MSM % content (10.80 ± 0.05) between CONT and BETA-groups at p < 0.01. The somatic cell count (SCC) was numerically higher (p = 0.47) in CONT-group compare than BETA-group. Overall, results demonstrated that supplementation of β-carotene do not change significantly productive parameters of lactating crossbred Sahiwal cows.